EVALUASI EFISIENSI TATA RUANG SEKOLAH MINGGU ANAK DI GKI SUNTER SEBAGAI SARANA EDUKASI DAN SOSIAL - Laura Tri Agustin; Jason Christian Adam; Johanna Teresa Verisya (Jurnal Serina Abdimas, 2026)
Early childhood education, encompassing both formal and informal settings such as Sunday schools, plays a crucial role in shaping quality individuals. An ergonomic learning environment is paramount for educational effectiveness and the holistic development of children's potential. This study addresses the challenge of enhancing the ergonomic comfort of Sunday school classrooms at Gereja Kristen Indonesia (GKI) Sunter, North Jakarta, particularly in the context of participant density and spatial limitations. The research aimed to (1) identify the current ergonomic comfort level of existing classrooms and (2) propose functional and safe spatial layouts for children. A participatory and evaluative approach was employed through three stages: data collection and field survey, problem mapping and analysis, and solution design and proposal. Survey findings revealed that fluctuating participant numbers posed a significant challenge to spatial arrangement. Based on this analysis, three alternative classroom layouts were developed, tailored to participant capacity and activity types: a "U" configuration for high density (maximum 30 children), an auditorium and cluster configuration for medium density (maximum 24 children), and a circular configuration for low density (maximum 18 children). These proposed configurations were designed by considering their respective advantages and disadvantages to foster a more comfortable and conducive learning environment that optimizes interaction and learning for the children attending GKI Sunter's Sunday school. Pendidikan anak usia dini, baik formal maupun informal seperti sekolah minggu, memegang peranan krusial dalam pembentukan individu berkualitas. Lingkungan belajar yang ergonomis sangat memengaruhi efektivitas pendidikan dan pengembangan potensi anak secara holistik. Studi ini berfokus pada peningkatan kenyamanan ergonomi ruang kelas sekolah minggu di Gereja Kristen Indonesia (GKI) Sunter, Jakarta Utara, yang menghadapi tantangan kepadatan peserta dan keterbatasan ruang. Penelitian ini bertujuan untuk mengidentifikasi tingkat kenyamanan ergonomi ruang kelas yang ada, serta merancang usulan tata letak ruang yang fungsional dan aman bagi anak-anak. Metode pelaksanaan menggunakan pendekatan partisipatif dan evaluatif melalui tiga tahapan: pengumpulan data dan survei lapangan, pemetaan dan analisis masalah, serta perancangan dan usulan solusi. Hasil survei menunjukkan bahwa variasi jumlah peserta sekolah minggu menjadi kendala utama dalam penataan ruang. Berdasarkan analisis, diusulkan tiga alternatif tata letak ruang kelas yang mempertimbangkan kapasitas peserta dan jenis kegiatan: konfigurasi "U" untuk kepadatan tinggi (maksimal 30 anak), konfigurasi auditorium dan kelompok untuk kepadatan sedang (maksimal 24 anak), dan konfigurasi lingkaran untuk kepadatan rendah (maksimal 18 anak). Ketiga konfigurasi ini dirancang dengan mempertimbangkan kelebihan dan kekurangan masing-masing untuk menciptakan lingkungan belajar yang lebih nyaman, kondusif, dan mendukung interaksi serta pembelajaran optimal bagi anak-anak sekolah minggu di GKI Sunter.